PENGOLAHAN ARSIP VERIFIKASI AKHIR SEBAGAI ARSIP VITAL DI UNIT PELAKSANA TEKNIS JAMINAN PEMELIHARAAN KESEHATAN MASYARAKAT DINAS KESEHATAN KABUPATEN SLEMAN - , RIFAN BAYU SAPUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Processing financial record are activities undertaken to process financial records are not organized into a regular. Then do the removal of the central file to the record center. Identify financial records as vital records. Then perform maintenance activities and maintenance records in the record center. This final report discusses the financial records management system as vital records that exist in Unit Pelaksana Teknis Jaminan Kesehatan Masyarakat Dinas Kesehatan Kabupaten Sleman focus more on financial records as vital records. Data collection methods include interviews, observation, participating in the management of inactive records, as well as collecting theories of library materials. This method is used to obtain the data correctly and accurately. The conclusion of this final report, Unit Pelasana Teknis Jaminan Kesehatan Masyarakat Dinas Kesehatan Kabupaten Sleman has not made the management of financial records have not been well managed. In addition to its management, there are still obstacles faced as limited facilities, where processing and lack of personnel who have knowledge of archives and archivists that exist in the Unit Pelasana Teknis Jaminan Kesehatan Masyarakat Dinas Kesehatan Kabupaten Sleman.